2001
DOI: 10.1080/00498250110043292
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of human CYP1A2 activityin vitroby methylxanthines: potent competitive inhibition by 8-phenyltheophylline

Abstract: 1. Humans are exposed in vivo to methylxanthines by dietary ingestion, as well as from their use as therapeutic agents. The inhibitory effect of a series of these compounds on high-affinity phenacetin O-deethylase activity in the human liver microsomal fraction, a measure of CYP1A2 activity, has been evaluated. 2. Paracetamol, the product of phenacetin O-deethylase activity, was analysed by gas chromatography/negative-ion mass spectrometry using a novel bistrifluoromethylbenzoyl/ trimethylsilyl derivative, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…P450 1A2 is highly inducable by exposure to polycyclic aromatic hydrocarbons, such as some present in cigarette smoke, charcoal grilled meat, diet containing compounds as indole derivatives, and some therapeutic drugs as omeprazole (87). Its active site is able to accommodate planar molecules of moderate volume and basicity [5,9]. Prominent inhibitors include some selective serotonin reuptake inhibitors and antiarrhythmics [10].…”
Section: P450 1a2mentioning
confidence: 99%
See 3 more Smart Citations
“…P450 1A2 is highly inducable by exposure to polycyclic aromatic hydrocarbons, such as some present in cigarette smoke, charcoal grilled meat, diet containing compounds as indole derivatives, and some therapeutic drugs as omeprazole (87). Its active site is able to accommodate planar molecules of moderate volume and basicity [5,9]. Prominent inhibitors include some selective serotonin reuptake inhibitors and antiarrhythmics [10].…”
Section: P450 1a2mentioning
confidence: 99%
“…Of the two non-substrates -haloperidol (7) and verapamil (19) -included in the test set, haloperidol (7) was wrongly assessed active. Of the P450 1A2 substrates, five tricyclic structures and mexiletine (9) were not included in the hitlist. A visual inspection of these false negative results showed that the tricyclic structures map perfectly the RA and the H feature; however, the HBA feature is not mapped.…”
Section: Ligand-based General Model For P450 1a2 Substratesmentioning
confidence: 99%
See 2 more Smart Citations
“…CYP1A2, like CYP3A4, catalyzes the metabolism of neutral/basic, lipophilic, or planar molecules with at least one hydrogen-bonding site, making both the furanocoumarin monomers and dimers candidates for an interaction with this enzyme. In addition to the compounds tested, flavonoids (Zhai et al, 1998;Murray et al, 2001), methylxanthines (Murray et al, 2001), grapefruit juice, 6Ј,7Ј-dihydroxybergamottin, bergamottin, and the naturally occurring dimers GF-I-1 and GF-I-4 (Tassaneeyakul et al, 2000) have been shown to be potent to moderate inhibitors of CYP1A2 activity, using phenacetin as the marker substrate. The increased selectivity of the 55EE analog suggests different orientations for the 5-and 8-substituted ring systems within the binding domains for CYP1A2 and CYP2C19.…”
Section: Discussionmentioning
confidence: 99%